If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -3 + 5y = 9 Reorder the terms: -3 + 2y + 5y = 9 Combine like terms: 2y + 5y = 7y -3 + 7y = 9 Solving -3 + 7y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 7y = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 7y = 9 + 3 7y = 9 + 3 Combine like terms: 9 + 3 = 12 7y = 12 Divide each side by '7'. y = 1.714285714 Simplifying y = 1.714285714
| 3x+3=5*2x+1 | | 2k^3+9k^2+23k=288 | | 7(t-3)+32t=9(t+1) | | -214-(-87)=x | | 6=-5/w-5 | | -10n=20 | | 1/2x=x+10- | | x+(x-18)=150 | | 3(2y-6)=-9(y-8) | | 13x+1y=25 | | [-2x+4]=4 | | -3[2t+1]=9 | | -10=-4v-v | | 8x+1=10-5x | | 3/4[8t-12]=6(t-1) | | 2x-5x=y | | a+bi+6(a-bi)=7 | | 27rst+27tsr= | | 3/4[8t-12]=6(1-1) | | 13+-7-10x=2 | | -5b=25 | | 12*90= | | 5+2(x-2)=18 | | v+3=-1 | | 9/4t^-1 | | (-4)(u+2)=((3)(2u+4))+4 | | 10=-4v-v | | [3z-2]+5=9 | | (f/2)-4=1 | | 112+2x=22-4x | | 2[4x+1]-5=1 | | -24=2x-x+6 |